HUBUNGAN ADVERSITY QUOTIENT DAN PRESTASI BELAJAR PADA MAHASISWA PROGRAM STUDI PSIKOLOGI UNIVERSITAS BM - Stefani Virlia (Universitas Bunda Mulia, 2015)
Education is one of the most important aspects of life for the individual. Education is an effort to realize the active learning process, and education also serves to develop the potential of learners. But in achieving that goal, the individual doesn’t escape from the difficulties or challenges. Basically, every individual has the ability to withstand the challenges / difficulties that are called by adversity quotient. Through research, researchers tried to see if there is a direct relationship between adversity quotient and learning achievement in psychology courses BM University. This study used quantitative research methods and belong to the type of correlational study. Data collection techniques used are AQ questionnaire from Stoltz (2007) and learning achievements obtained from the IP (GPA). The results obtained are no direct relationship between adversity quotient and student learning achievement in psychology courses at UBM with r = .134 (p> .05 ). Students of Psychology Faculty fall into the category Campers because it has tended to have moderate levels of AQ. Gender and age did not show any significant difference to the level of AQ. This study shows that students tend to give up easily and pessimistic when challenges or difficulties growing. Keywords: Adversity Quotient, Learning Achievement, Students